Human interaction with the environmental ecosystem: a review, some notes and insights - Yap, Chee Kong; Chee, Seng Leow; Shih, Hao Tony Peng; Ismail, Mohamad Saupi (Insight Medical Publishing, 2020)
The present review focused on the human interaction with the environmental ecosystem. Based on the present review, it is concluded that human interaction on our ecosystem is broadly reported in the literature. By using the model of human interaction with the environment that was firstly recommended by Hammond (1995), the Life Support interaction is focussed and discussed. From the negative picture from the human interaction on the ecosystem concept, a lot of human activities from the past and future are involved. These anthropogenic activities include deforestation depleting food and medicinal resources, the growing world energy demand on non-renewable sources, active transportation, point and non-point sources that create environmental pollution and contaminating the ecosystem in terms of food and clean water supply. In addition, enrichment of the hazardous chemicals in our environmental ecosystem is inarguably contributed by human interactions as the root cause. This is related to human behaviours that have impacted on human welfare which is a prevalent predicament to be solved nowadays.